FAKTOR-FAKTOR YANG MEMENGARUHI ABNORMAL RETURN PADA KINERJA JANGKA PANJANG - Agus Hilal; Syafnita Syafnita; Amalia Ilmiani (Fakultas Ekonomi Universitas Pekalongan, 2018)
This study aims to examine and analyze the influence of benchmark, size of firm, market value, money raised and magnitude of underpricing against abnormal returns of shares in long-term performance after 3 years of IPO. Independent variables in this study benchmark, size of firm, market value, money raised and magnitude of underpricing. Dependent variable is Abnormal Return on long term performance stock after 3 years IPO. The sample of research used is service company that conducts IPO period of 2013 & 2014 as 27 service companies by using purposive sampling method. Analytical technique used is multiple linear regression analysis and tested the classical assumption which includes normality test, multicolinearity test, autocorrelation test, and heteroskesdasticity test. The results showed that partially Benchmark does not significantly effect to Abnormal Return; Size of Firm, Market Value and Magnitude of Underpricing have a significant effect on Abnormal Return; Money Raised has no significant effect on Abnormal Return. Keywords: Benchmark, Size of Firm, Market Value, Money Raised, Magnitude of Underpricing, Abnormal return